Faktor-Faktor yang Mempengaruhi Penerapan Peraturan Daerah Kabupaten Gorontalo Nomor 04 Tahun 2014 Tentang Penertiban Hewan Ternak di Desa Ilomata, Kecamatan Bilato - Cici Cahyani Lamunte; Erman I. Rahim; Julius T. Mandjo (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
This study aims to analyze the factors influencing the implementation of Regional Regulation of Gorontalo Regency Number 04 of 2014 concerning the Control of Livestock in Ilomata Village, Bilato District. This research employs an empirical legal method with a sociological juridical approach to examine law not only as written norms but also as a social practice within society. Data were collected through interviews with village officials, regional regulation enforcement officers, and livestock owners, as well as through documentation and literature studies. The collected data were analyzed qualitatively using Lawrence M. Friedman’s legal system theory and Soerjono Soekanto’s theory on factors influencing law enforcement. The results indicate that the implementation of the regional regulation has not been optimal. The influencing factors include legal substance, legal structure (law enforcement officers), facilities and infrastructure, community factors, and legal culture. Normatively, the regulation contains clear provisions; however, its implementation is hindered by inconsistent enforcement, limited supporting facilities, and low levels of public legal awareness. Legal culture and the lack of consistency among law enforcement officers are the most dominant factors affecting the effectiveness of the regulation’s implementation. Therefore, it is necessary to strengthen consistent law enforcement, improve supporting facilities, and undertake continuous efforts to build public legal awareness in a participatory manner.